Períodos de estratificação na germinação de sementes de alface (Lactuca sativa L.) sob diferentes condições de luz e temperatura - Bufalo, Jennifer [UNESP]; Esteves Amaro, Amanda Cristina [UNESP]; de Araujo, Humberto Sampaio; Corsato, Jaqueline Malagutti [UNESP]; Ono, Elizabeth Orika [UNESP]; Ferreira, Gisela [UNESP]; Rodrigues, Joao Domingos [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Lettuce seeds have a high sensitivity to variations in humidity and temperature of the environment where they germinate, therefore, studies with the aim of improve the germination and physiological performance of these have been conducted. Thus, the study aimed to evaluate the efficiency of pre-germination treatment stratification (5 degrees C) for different periods, and increase the uniformity of germination of lettuce seeds submitted to different conditions of light and germination temperatures. In the pre-germinative treatment, the seeds of lettuce (Lactuca sativa L.) var. American Great Lakes were placed in plastic boxes dark of the type "gerbox" and subjected to temperature stratification of 5 degrees C and the dark for 0, 4, 8, 12 and 16 hours. After periods of stratification the seeds were submitted to germination tests which were transferred to plastic boxes type "gerbox" transparent (constant light) and dark (no light) and were maintained in a germination chamber B.O.D with light constant at temperatures of 20, 25, 30 and 35 degrees C. The design used was the entirely randomized with four repetitions, in a factorial outline 5x4x2, five pre-germinative treatments, four germination temperatures and two light conditions. Stratification for 16 hours and temperatures of 20 and 25 degrees C stimulated the germination of lettuce seeds, providing a higher germination percentage, germination speed index and minor mean germination time. The presence of light resulted in increased germination at 0, 4, 8 and 12 hours of stratification.
Stratification periods in seeds germination of lettuce (Lactuca sativa L.) under different conditions of light and temperature
Keywords: Lactuca sativa; light; temperature